Quality Function Deployment Implementation Based on Kano Model An Application on Mobile Vendor Product Development - Rusdiyantoro Rusdiyantoro; Yunia Dwie Nurcahyanie (Fakultas Teknik , Universitas PGRI Adi Buana Surabaya, 2011)
The severe competition in the market has driven enterprises to produce a wider variety of products to meet consumers’ needs, a strategic business system allows more effective communication among different groups at dispersed locations to share ideas and access information needed for developing new productsand executing innovative processes. The mainfunction of mobile vendor product development is to develop an attractive system which ensures customer satisfaction. Therefore, one of the important topics of the system developments is to take customer requirements into consideration.Quality function deployment (QFD) has beenwidely used for numerous years; it is one ofthe structured methodologies that are usedto translate customer needs into specific qualitydevelopment. However, in the traditional QFD approach, each element’s interdependence and customer requirements are usually not systematically treated. Additionally, the Kanomodel can effectively classify customer demandattributes, but to make Kano model moreobjective in the course of weighing.